Bacterial and fungal infectious complications in the immediate and early periods of transplantation - I. A. Kurmukov (Трансплантология (Москва))
The review presents data on the recent change in the spectrum of bacterial and fungal infectious complications in the early posttransplantation period. It discusses some reasons for this change. The emergence of multidrug-resistant strains of infectious complications requires epidemiological studies of the spectrum of nosocomial pathogens at the specific organ transplant centers and health care facilities where potential organ donors are present. Peritransplantation antibiotic prophylaxis and empiric antibiotic therapy should be based on either the results of these studies or the combined use of antibiotics that overlap the spectrum of the most dangerous causative agents.